(3eONd efgLj (B-(3JWHjbjs - (3Ydj adGM(B, (3GdRYHjs ((3YeGf(B:s (3OGQ UaGA(B,s, 2009)
(3GdJShjb (B: (3CSS h eaGgje , GdHjFI GdJShjbjI , GdShb , GdeSJgdc h Sdhcg GdTQGFj , HMhK GdJShjb , fXe GdeYdheGJ GdJShjbjI , GSJQGJjLjI GdefJLGJ h GdJSYjQ , GSJQGJjLjI GdJQhjL h GdGJUGdGJ GdJShjbjI , GSJQGJjLjI GdJhRjY , GdQaGgI GdGbJUGOjI , GdJfejI GdGLJeGYjI , fLGM GdTQcGJ h GdefXeGJ , GSJQGJjLjI GdNOeGJ , GdJShjb GdGdcJQhfj (B.s
(3eQGLY U(B.417(3; edGMb U(B.379((3GbJfGAGJ (B2014 3(3f(B)s
Keywords: (3COGQI GdeHjYGJs; (3GdJShjbs; (3GdJShjb GdGdcJQhfjs; (3GdJhRjYs